2017
DOI: 10.1016/j.ijdevneu.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in inter‐alpha inhibitor protein expression after hypoxic‐ischemic brain injury in neonatal rats

Abstract: Hypoxic-ischemic (HI) brain injury is frequently associated with premature and/or full-term birth-related complications that reflect widespread damage to cerebral cortical structures. Inflammation has been implicated in the long-term evolution and severity of HI brain injury. Inter-Alpha Inhibitor Proteins (IAIPs) are immune modulator proteins that are reduced in systemic neonatal inflammatory states. We have shown that endogenous IAIPs are present in neurons, astrocytes and microglia and that exogenous treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Inflammatory responses in the fetal systemic and central nervous systems (CNSs) appear to contribute to the development of many types of brain injury in the newborn (Ferriero, 2004). Furthermore, we previously reported time-dependent changes in the endogenous expression of IAIPs in the brain after exposure to hypoxia-ischemia and hypoxia alone in neonatal rats (Disdier et al, 2018) and in the cerebral cortex and cerebellum of fetal sheep after exposure to brain ischemia (Spasova et al, 2017). Studies have also suggested that IAIPs could be important in neuroplasticity (Duman, Aghajanian, Sanacora, & Krystal, 2016;Gaudet, Lim, Stonestreet, & Threlkeld, 2016;Goldschmied & Gehrman, 2019;Normann, Schmitz, Furmaier, Doing, & Bach, 2007;Popoli, Gennarelli, & Racagni, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory responses in the fetal systemic and central nervous systems (CNSs) appear to contribute to the development of many types of brain injury in the newborn (Ferriero, 2004). Furthermore, we previously reported time-dependent changes in the endogenous expression of IAIPs in the brain after exposure to hypoxia-ischemia and hypoxia alone in neonatal rats (Disdier et al, 2018) and in the cerebral cortex and cerebellum of fetal sheep after exposure to brain ischemia (Spasova et al, 2017). Studies have also suggested that IAIPs could be important in neuroplasticity (Duman, Aghajanian, Sanacora, & Krystal, 2016;Gaudet, Lim, Stonestreet, & Threlkeld, 2016;Goldschmied & Gehrman, 2019;Normann, Schmitz, Furmaier, Doing, & Bach, 2007;Popoli, Gennarelli, & Racagni, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Post-ischemic neuroinflammation in the immature brain is a key pathophysiological factor in the development of HI-related injury [1316]. However, the course of the inflammatory process has been investigated only partly in the neonatal setting [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…HI decreases tight junctions at the BBB and increases barrier permeability to hydrophobic compounds in the fetal and neonatal brain [73][74][75][76]. Nonetheless, the level of exogenously administered IAIPs that could cross the BBB under conditions of HI could remain low relative to the quantity of IAIPs endogenously present within the brain parenchyma [77,78]. The presence of high levels of endogenous IAIPs within the brain parenchyma raises the question of whether influx transport systems exist for either IAIPs or certain IAIP subunits [39,79].…”
Section: Iaip Transfer Into the Brainmentioning
confidence: 99%